PENINGKATAN PENGELOLAAN POSYANDU, PENGETAHUAN DAN KETRAMPILAN KADER DALAM PENANGANAN DIABETES MELLITUS - Noviyanti, Retno Dewi; Wijayanti; Dodik Luthfianto; Agung Setya Wardana; Safira Faza Azhari; Puji Sri Lestari (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The number of elderly people nationally and internationally tends to increase every year, one of the non-communicable diseases that elderly people often experience is diabetes mellitus (DM). Even though DM is a chronic disease that does not cause death directly, it can have fatal consequences if it is not managed properly. Management of DM requires multidisciplinary treatment which includes non-drug therapy and drug therapy. One of the non-drug therapies is rice bran varieties Situbagendit and IR64. Partner problems include the implementation of posyandu not being optimal, inadequate infrastructure, limited health examination tools, limited number of cadres, lack of knowledge of cadres and the discovery of elderly people suffering from DM. The aim of the activity is to overcome partner problems by increasing the knowledge and skills of posyandu cadres regarding management of posyandu for the elderly, nutrition and DM diet for the elderly, training in making processed rice bran varieties IR64. The methods used in this service are one group pretest posttest design, lectures and discussions, group discussions, demonstrations, providing supporting tools. Location of Salak Songgorunggi Posyandu Dagen Jaten Karanganyar. Time is September 2023. Data analysis technique uses Wilcoxon. The average knowledge results before education were 74.5 ± 1.09 and after education 89.0 ± 6.41, with an average increase in value of 14.5. The results of the difference test obtained a value of p = 0.000. The conclusion is that there is a difference in the value of knowledge before and after providing education.